Anticoagulant Activity in Cell-Free Peritoneal Fluid of an Experimental Pancreatic Ascites Tumor - Ts’ao, C; Galluzzo, T S; Hart, S J; Ng, A S; Sorenson, P G; Subbarao, V (Thrombosis and Haemostasis, 1985)
The ascitic form of a chemically-induced pancreatic ductal adenocarcinoma in the Syrian golden hamster was very bloody and indistinguishable from blood macroscopically. Unlike blood, the bloody fluid remained unclotted at room temperature. To explore the possibility of presence of anticoagulants, we mixed 40% cell-free fluid with 60% normal human plasma and tested the clottability of the mixture with standard techniques. Plasma containing the fluid showed markedly prolonged activated partial thromboplastin time (APTT), thrombin time (TT) and recalcification time (RCT), and normal prothrombin time (PT) and reptilase time (RT). Comparing the prolongation of APTT of samples containing the fluid to those containing a commercial heparin, the fluid contained an anticoagulant activity equivalent to 0.436 ± 0.03 unit heparin per ml (mean ± SEM, n = 14). In addition to prolonging the APTT, TT and RCT, the fluid also inhibited the clotting and amidolytic activities of thrombin. “Heparsorb” had nearly completely neutralized the anticoagulant activity in fluid samples, while protamine sulfate was only partially effective. Incubation of fluid with pronase or phospholi-pase did not affect its anticoagulant activity; incubation with heparinase had only a minimal effect. Electrophoresis of an alkali digested fluid on cellulose acetate revealed the presence of heparan sulfate. The native ascitic fluid also contained other hemostatic components including platelets, fibrinogen and antithrombin III, but their concentrations were much lower than in blood. Apparently, heparan sulfate in the neoplastic effusion is largely responsible for the bloody ascites tumor remaining unclotted.
Keywords: Experimental pancreatic adenocarcinoma; Neoplastic effusion; Anticoagulant; Heparan sulfate